Ned Kelly [videorecording (DVD)] - Badelt, Klaus (Universal, 2003)
Sixteen-year-old Irish immigrant Ned Kelly is sentenced to three years in prison for stealing horse. After his release, he finds work tending to horses owned by Richard Cook, whose wife becomes interested in Ned. Fitzpatrick, is a police officer interested in Ned's sister Kate. When she refuses his advances, Fitzpatrick steals the family's animals. Not being able to go straight, Ned goes on the run and steals from a string of banks to support himself and his gang.